alfi rahmaini dkk Islamization in the indonesian archipelago: acculturation of islamic culture and tradition (Journal of Communication and Multidisciplinary studies, 2026)
This paper reviews the history of the entry and development of Islam in the archipelago which took place peacefully and gradually between the 7th to the 16th centuries AD. The process of Islamization is carried out through various main channels, namely trade, marriage, da'wah, politics, education, and Sufism. The main focus of the discussion lies in the phenomenon of acculturation, where Islamic values blend harmoniously with the local Hindu-Buddhist culture and indigenous beliefs, giving birth to a moderate and tolerant identity of "Islam Nusantara". In Java, the role of Wali Songo is central in integrating religious teachings through an artistic and cultural approach. Meanwhile, in North Sumatra, the Barus area and the Sultanate of Deli became an important starting point for the spread. The impact of this process is documented in various physical and non-physical relics, ranging from the distinctive architecture of mosques, palace structures, tomb traditions, to literary works and calligraphy art. This history proves that the success of Islam in Indonesia is inseparable from its ability to adapt to local wisdom without losing the essence of its spiritual teachings.